1971
DOI: 10.1029/jb076i002p00570
|View full text |Cite
|
Sign up to set email alerts
|

Voigt and Reuss prediction of anisotropic elasticity of dunite

Abstract: Aggregate anisotropic elastic constants were calculated for two nearly mono‐minerallic dunites by both the Voigt and the Reuss averaging schemes. The average constants were obtained rigorously from petrofabric data, which provided precise orientation of a sample of 100 grains in each specimen, by using published values of olivine single‐crystal constants. The resultant elastic constants were used to calculate P‐ and S‐wave phase velocities in various directions for comparison with actual measurements made in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(59 citation statements)
references
References 19 publications
2
57
0
Order By: Relevance
“…Bunge 1982;Ben Ismail & Mainprice 1998). Due to stress/strain compatibility assumptions, three different averaging schemes are possible (Crosson & Lin 1971). The constant strain or Voigt (V) average (Voigt 1928) and constant stress or Reuss (R) average (Reuss 1929) provide upper and lower bounds.…”
Section: Methodsmentioning
confidence: 99%
“…Bunge 1982;Ben Ismail & Mainprice 1998). Due to stress/strain compatibility assumptions, three different averaging schemes are possible (Crosson & Lin 1971). The constant strain or Voigt (V) average (Voigt 1928) and constant stress or Reuss (R) average (Reuss 1929) provide upper and lower bounds.…”
Section: Methodsmentioning
confidence: 99%
“…In ultramafic and metamorphic rocks, numerous authors have shown that acoustic anisotropy can be explained by preferred orientation of anisotropic minerals (Crosson and Lin, 1971;Baker and Carter, 1972;Brocher and Christensen, 1990). Calcite is a highly anisotropic mineral in which the P-wave velocity parallel to the oaxis is 5.6 km/s whereas P-wave velocity perpendicular to the c-axis is 7.4 km/s (Dandekar, 1968).…”
Section: Mineral Orientationmentioning
confidence: 99%
“…Using an interactive program (Mainprice, 1990), the procedure for the calcula tion of seismic phase velocities uses the Christof fel equation and has been described in detail by Crosson and Lin (1971) and Peselnick et al (1974). This explains the only monoclinic symmetry of the diagrams.…”
Section: Calculations Of Sws From Petrofabric Datamentioning
confidence: 99%